TEKNIK NURSERY DAN OUT-PLANTING SEBAGAI UPAYA PELESTARIAN MANGROVE DI DUSUN SIUNG, SEKOTONG, LOMBOK BARAT - Ibadur Rahman; Fadillah, Fitri; Devi, Lokita; Z, Muhammad Fayyadh A.; Sultansyah, Muhammad; Siahaya, Patrick Alexander; Ta'yuni, Qur'a; Asmileen, Suci Dwi; Utami, Widia Tri; Jefri, Edwin; Wahyudi, Rhojim; Damayanti, Ayu Adhita; Himawan, Mahardika Rizqi; Lestrariningsih, Wiwid Andriyani; Buhari, Nurliah; Larasati, Chandrika Eka; Siagian, Raja Aditya Sahala; Putra, Brilliant Rudzaky Ridwan (Universitas Mataram, 2024)
Mangroves play a crucial role in maintaining environmental balance, including wave attenuation, preventing erosion, providing habitat for various species, and storing carbon to mitigate climate change. However, mangrove ecosystems are currently facing serious degradation threats due to human activities and climate change, necessitating protective measures, rehabilitation, and active community participation to ensure their preservation. This community service initiative aims to conserve mangrove ecosystems through nursery activities (nursery) and mangrove planting (out-planting) in potential areas not yet populated by mangroves in Siung Village, Sekotong, West Lombok. The nursery activities include techniques for collecting seedlings from the wild, selecting and sorting healthy seedlings, placing them in planting media, and caring for the seedlings. Meanwhile, the out-planting activities involve planting the seedlings in the wild and monitoring the planted mangroves to ensure their survival. Over approximately two months, this project has produced 3,200 mangrove seedlings of Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa, and Ceriops tagal species, with a survival rate of 87.5%. As for the out-planting activities, 2,700 mangrove seedlings have been successfully planted in areas near the nursery site. Challenges encountered during seedling collection and care include tidal fluctuations, the presence of pests and predators. In the out-planting activities, ongoing monitoring and maintenance are required to maintain a high survival rate for the seedlings planted in the wild.